AVALIAÇÃO DA EVOLUÇÃO GENÉTICA DO REBANHO COMO GESTÃO DE MATRIZES - BARONI, Guilherme da Silva; FERRAZ, André Luiz Julien; LECA FERREIRA, Luana; FIGUEIREDO, Ana Paula Aquino de (ANAIS DO ENIC, 2025)
-